Characteristics of vaccinating providers reported through Medicare claims in office-based settings: Volume of influenza and pneumococcal vaccinations. Issue 1 (3rd January 2020) - Shen, Angela K.; Warnock, Rob; Selna, Weston; MaCurdy, Thomas E.; Chu, Steve; Kelman, Jeffrey A.
Abstract: Vaccination coverage among older adults is low in the United States. A recommendation from a provider is a strong predictor of vaccine receipt. Using Medicare Fee-For-Service data (2015–2017) this study characterized providers by the number of influenza and pneumococcal vaccines administered in physician offices, age, gender, and professional specialty to determine the volume of vaccines provided by individual providers and characteristics of these providers. Half of all vaccinations were provided by 10% of providers. The mean age of 224, 483 and 165, 710 unique influenza and pneumococcal providers respectively was 49 years (SD: 12 years) with males and females equally distributed. The highest vaccinating quartile of providers tended to be older, more likely male and more likely general physicians. Those who administered a high volume of one vaccine were likely to administer a high volume of the other. Providers administering vaccines in office-based settings can do more to increase vaccination coverage rates.